Molecular Simulation of Hydrogen Storage in Ion-Exchanged X Zeolites - Xiaoming Du (Advances in Materials Science and Engineering)
Grand Canonical Monte Carlo (GCMC) method was employed to simulate the adsorption properties of molecular hydrogen on ion-exchanged X zeolites at 100–293 K and pressures up to 10 MPa in this paper. The effect of cation type, temperature, and pressure on hydrogen adsorption capacity, heat of adsorption, adsorption sites, and adsorption potential energy of ion-exchanged X zeolites was analyzed. The results indicate that the hydrogen adsorption capacity increases with the decrease in temperatures and the increase in pressures and decreases in the order of KX<LiX<CaX. The isosteric heat of adsorption for all the three zeolites decreases appreciably with the increase in hydrogen adsorption capacity. The hydrogen adsorption sites in the three zeolites were determined by the simulated distribution of hydrogen adsorption energy and the factors that influence their variations were discussed. Adsorption temperature has an important effect on the distribution of hydrogen molecules in zeolite pores.